Declines and pronounced regional disparities in meperidine use in the United States - Boyle, John M. (Pharmacol Res Perspect, 2021)
There have been increasing concerns about adverse effects and drug interactions with meperidine. The goal of this study was to characterize meperidine use in the United States. Meperidine distribution data were obtained from the Drug Enforcement Administration's Automated of Reports and Consolidated Orders System. The Medicare Part D Prescriber Public Use File was utilized to capture overall trends in national prescriptions in this observational report. Nationally, meperidine distribution decreased by 94.6% from 2001 to 2019. In 2019, Arkansas, Alabama, Oklahoma, and Mississippi saw significantly greater distribution when compared with the US state average of 9.27 mg per 10 persons (SD = 6.82). Meperidine distribution showed an 18‐fold difference between the highest state (Arkansas = 36.8 mg) and lowest state (Minnesota = 2.1 mg). Five of the six states with the lowest distribution were in the Northeast. Meperidine distribution per state was correlated with the prevalence of adult obesity (r(48) = +0.48, p < .001). Family medicine and internal medicine physicians accounted for 28.9% and 20.5%, respectively, of meperidine total daily supply (TDS) in 2017. Interventional pain management (5.66) and pain management (3.48) physicians accounted for the longest TDS per provider. The use of meperidine declined over the last two decades. Meperidine varied by geographic region with south‐central states, and those with more obesity, showing greater distribution. Primary care doctors continue to account for the majority of meperidine daily supply. Increasing knowledge of meperidine's undesirable adverse effects like seizures and serious drug–drug interactions is likely responsible for these pronounced reductions.